Molecular dynamics simulation of urea adsorption on various nanoparticles in a spiral microfluidic system (Publication with Expression of Concern. See vol. 166, 2024) - Jokar, Zahra; Khademiyan, Afrouz; Fallah, Mohammad-Amir; Smida, Kamel; Sajadi, S. Mohammad; İnç, Mustafa (Elsevier Sci Ltd, 2022)
Microfluidic devices use the physical-chemical features of liquids at a microscale. Microfluidics allow the analysis and employment of fewer volume of specimens and chemicals reducing the cost of applications. A kidney failure will lead to the accumulation of urea toxins in blood and eventually result in patient death. End-stage renal disease (ESRD) occurred when kidneys destructed completely. In this comparative study, a spiral Microfluidic system with an adsorption section is modeled with coated needles. For coated section, various new nanoparticles have been introduced to assess their capability in urea adsorption. Molecular dynamic (MD) technique was applied to assess Urea adsorption capability of nanoparticles. Comparative investigation was accomplished among Boron-Carbon-Nitride Nanolayer (BCN-Nanolayer), Boron-Carbon-Nitride Nanotube (BCN-Nanotube), Graphene (GNP), Carbon Nanotube (CNT), Zeolite Y, Zeolite Z, and Zeolite ZSM5 nanoparticles. In this study, 7 different analyses including Gibbs free energy, Solvent accessible surface area (SASA), root mean square deviation (RMSD), radial distribution function (RDF), radius of gyration (Rg), number of hydrogen bonds, and interaction energy have been utilized for testing urea adsorption performance of nanoparticles. Among all mentioned adsorbents, BCN-Nanotube and BCN-Nanolayer adsorbed urea molecules better in comparison with other studied adsorbents, especially Zeolite group nanoparticles.
Keywords: Nanoparticles; Molecular dynamics simulation; Microfluidic system; Urea; Adsorption; End-stage renal disease